Photochemically-generated intermediates in synthesis - Albini, Angelo; Fagnoni, Maurizio (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
This book fills a gap between physical organic photochemistry and photochemistry applied to organic synthesis. It focuses on photoreactions involving an intermediate that has been (or at least may be) generated and where mechanistic aspects control the course of a reaction and its synthetic value. The first chapter presents general aspects, and each of the following chapters contains a short introduction with the key kinetic data for typical intermediates and reference to mechanistic work. The sections of each chapter then consider the various aspects of the topics: radicals, cations, carbenes, and nitrenes.
Photogenerated intermediates : principles and practice -- Photogeneration of carbon centered radicals -- Photogeneration of heteroatom-centered radicals -- Photogeneration of biradicals and radical pairs -- Photochemical generation of radical ions -- Photogeneration of carbocations and carbanions -- Photogeneration of carbenes and nitrenes -- Manipulating intermediates the photochemical way.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Carbocations; Carbanions; Intermediates (Chemistry); Photochemistry; SCIENCE -- Chemistry -- Organic; Carbanions; Carbocations; Intermediates (Chemistry); Photochemistry; Organische Synthese; Zwischenstufe; Photochemische Reaktion; Radikal; Carbocations; Electronic books; Electronic books; Electronic books